Cardiomyogenesis Modeling Using Pluripotent Stem Cells: The Role of Microenvironmental Signaling - Leitolis, Amanda; Robert, Anny W.; Pereira, Isabela T.; Correa, Alejandro; Stimamiglio, Marco A. (Frontiers in Cell and Developmental Biology, 2019)
Pluripotent stem cells (PSC) can be used as a model to study cardiomyogenic differentiation. In vitro modeling can reproduce cardiac development through modulation of some key signaling pathways. Therefore, many studies make use of this strategy to better understand cardiomyogenesis complexity and to determine possible ways to modulate cell fate. However, challenges remain regarding efficiency of differentiation protocols, cardiomyocyte (CM) maturation and therapeutic applications. Considering that the extracellular milieu is crucial for cellular behavior control, cardiac niche studies, such as those identifying secreted molecules from adult or neonatal tissues, allow the identification of extracellular factors that may contribute to CM differentiation and maturation. This review will focus on cardiomyogenesis modeling using PSC and the elements involved in cardiac microenvironmental signaling (the secretome - extracellular vesicles, extracellular matrix and soluble factors) that may contribute to CM specification and maturation.